Analisa Metode Pembayaran Dalam Merger Dan Akuisisi Terhadap Abnormal Return Saham Go Public Di Bursa Efek Jakarta - , Mayasari, Dr. Mamduh M. Hanafi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Research on the effects of is mergers and acquisitions have been frequently undertaken. The result of that research is also varied but the research is focused on a different subject. The result that generally occurs from the merger and acquisition is an abnormal return, before and after the announcement. Abnormal return prior to the merger and acquisition announcement was also effected by the method of payment that would be done in the merger and acquisition. In this research we focus on companies that do corporate actions in mergers and acquisitions from 2005 to 2007. With a total sample of 16 companies. Overall, the outcome from this research shows an insignificantly abnormal return for method of payment using cash and an exchange of shares in the merger or acquisition.